Transforming the Four Pillars of Holistic Marketing in the Social Media Ecosystem: Systematic Literature Review 2020-2026 - Amalia Fatia; Tiara Asti Meida; Silvi Yuniar; Veronika Joan Jasmine (Athallah Publishing Globalindo, 2026)
The development of social media as a business ecosystem has driven a paradigm shift in marketing from a partial approach to an integrated holistic approach. The concept of holistic marketing introduced by Kotler and Keller, with its four pillars including relationship, internal, integrated, and societal marketing, offers a relevant framework for understanding this transformation. However, there is no systematic synthesis that links the framework to social media marketing practices, especially in the context of developing countries such as Indonesia. This study aims to map the development of research on the application of holistic marketing through social media in the period 2020-2026 using the Systematic Literature Review (SLR) method with the PRISMA protocol. Of the 60 articles identified through Google Scholar, Garuda, and OpenAlex, as many as 20 articles met the inclusion criteria for thematic analysis. The results of the synthesis identified four main themes the dominance of relationship marketing that transformed into community-driven engagement; the transition of integrated marketing from traditional IMC to data-based omnichannel; (3) the shift of societal marketing from CSR as an add-on to a core strategy; and internal marketing as the least underrepresented pillar, creating asymmetry in the implementation of holistic marketing. The conceptual contribution of this article is the first synthesis to connect Kotler's four-pillar framework to the social media ecosystem, while providing a future research roadmap for the development of holistic marketing in the digital age.